Measuring Democracy in Design for Migrant and Refugee Skills Recognition (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
Using two international case studies (Kingdom of Saudi Arabia’s Skills Verification Program (SVP) and Armenia’s national plan for recognizing the skills of refugees from Nagorno-Karabakh), this paper demonstrates how the recognition of prior learning (RPL) can serve as a critical tool for empowering individuals, particularly migrants and refugees, by facilitating access to education, employment, and social mobility. This analysis highlights the importance of policy alignment, system readiness, assessment practices, and pre/post-support structures in ensuring that RPL through a human-centered design approach (which prioritizes individual agency over rigid institutional structures) meaningful participation rather than reinforcing bureaucratic barriers. The author argues that RPL, when intentionally designed with a focus on democracy and individual empowerment, has the potential to transform labor market integration and lifelong learning opportunities. The paper concludes with recommendations for refining RPL frameworks to maximize their support of marginalized populations.